The Dynamic Interaction between Equity Prices and Supply Shocks - Jakob B. Madsen (University of Copenhagen, Economic Policy Research Unit (EPRU), 2003)
This paper develops a theory of medium term share price movements under slow adjustment in the labour market relative to the share market and perfect foresight in the share market. The model seeks to explain the slow movements in real share prices that have been observed in the OECD countries over the past 130 years. Using 130 years of data for the OECD countries, the empirical evidence indicates that movements in factor shares are crucial determinants of medium-term movements in share prices.
Keywords: G12; E31; E43; 330; share prices; supply shocks; rational expectations; Börsenkurs; Aktienmarkt; Gesamtwirtschaftliches Angebot; Schock; Industriestaaten